Integrating Role Play and Audio-Visual Media to Boost Speaking Skills: A Study of Eighth Graders at SMP Lab School Untad Palu - Fanisha Astri Aulia; Darmawan Darmawan; Desrin Lebagi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the effectiveness of using role play combined with audio-visual media to improve the speaking skills of eighth-grade students at SMP Lab School UNTAD Palu. The research was conducted in response to students’ difficulties in speaking English, such as limited vocabulary, incorrect pronunciation, and lack of self-confidence. A quantitative approach with a quasi-experimental design was used, involving two groups: an experimental group and a control group. Both groups were given a pre-test and a post-test to measure their speaking performance before and after the treatment. The collected data were analyzed using SPSS software. The results showed that the experimental group made significant progress in their speaking skills, with the average score increasing from 60.00 in the pre-test to 82.11 in the post-test. In contrast, the control group showed only a small improvement, from 59.41 to 67.71. Statistical analysis confirmed that the use of role play supported by audio-visual media had a significant positive effect on students’ speaking abilities, particularly in improving their fluency and accuracy.